Potential risk of infection transmission during storage and transplantation of hematological progenitor cells. Safety assurance - Bláha, M; Mĕricka, P; Stĕpánová, V; Malý, J; Vávra, L; Jebavý, L (Folia microbiologica, 2003)
In a group of 71 patients and 22 donors the danger of infection transmission by infusion of cryopreserved peripheral blood progenitor cells to the patient and/or cross contamination of stored grafts was evaluated. No laboratory signs of active infection were found in 15 donors (13 related, 2 unrelated; 68%) and in 55 patients (77%). Active infection by herpesviruses was the most common (in 13 patients and 7 donors), hepatitis B being found in only one case. The cytomegalovirus IgG test was the most common marker of previous infection; it was found in 14 donors and 55 patients. The rate of clinically unsuspected infections in donors and patients including cases requiring immediate treatment among the patients group is relatively high and fully justifies the practice of prophylactic serological testing in the whole range of tests according to the European Blood and Marrow Transplantation Group and International Society for Hematotherapy and Graft Engineering in both autologous and allogeneic transplantations of hematopoietic stem cells.
Keywords: Transplantation, Homologous; transplantace kostní dřeně; transplantace hematopoetických kmenových buněk; bezpečnost; homologní transplantace; lidé; sérologické testy; Bone Marrow Transplantation; infekce; Safety; Humans; kryoprezervace; autologní transplantace; Transplantation, Autologous; Serologic Tests; Cryopreservation; Hematopoietic Stem Cell Transplantation; Infections